ANALISIS MODEL PENGGUNAAN DOMPET DIGITAL PADA KALANGAN MAHASISWA PROGRAM STUDI MATEMATIKA FMIPA UNIVERSITAS TANJUNGPURA - AZ ZAHRA, URAY NUR AFIFAH; PRIHANDONO, BAYU; PASARIBU, MELIANA (E-Jurnal Matematika; Vol 13 No 3 (2024)DO - 10.24843/MTK.2024.v13.i03.p459, 2024)
Due to changes in the payment system caused by technological advancements in Indonesia, Bank Indonesia developed the Indonesia Payment System Blueprint 2025. This formulation focuses on initiatives to create a robust ecosystem that will steer the growth of digital finance in Indonesia, which is the ultimate goal of Bank Indonesia's long-term policy orientation. Bank Indonesia established the National Non-Cash Movement to provide a safe, effective, and seamless payment system. The purpose of this study is to examine the model of digital wallet usage and interpret the use of digital wallets among mathematics students at FMIPA Tanjungpura University. The modeling process begins with selecting parameters and forming assumptions to produce a mathematical model in the form of differential equations, finding equilibrium points, and conducting simulations. Data were obtained from questionnaires about the use of digital wallets distributed to 137 mathematics students in 2019–2022. Interpretation of the model of digital wallet usage among students of the Mathematics Study Program FMIPA Tanjungpura University obtained a cash payment-free equilibrium point obtained as  = ( , , ) = (20.550,0,0) and obtained that the population of students who have the potential to use digital wallets has increased and the population of students who use cash payments has also increased due to the factor of digital wallet balances that have run out and make payments in cash, resulting in a decrease in the population of students who have used digital wallets.